THE EFFECT OF FINANCIAL INCLUSION ON THE PERFORMANCE OF MSMES IN NORTH SUMATERA WITH FINANCIAL LITERACY AS A MEDIATION - Syaifuddin, Syaifuddin; Rosmaneliana, Dina; Toni, Nagian; Aktar, Salim; Siregar, Robert Tua (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2026)
This study aims to examine the effect of financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs), with financial literacy acting as a mediating variable. MSMEs play a vital role in economic growth; however, many business owners face challenges related to limited access to financial services and inadequate financial knowledge. This research employs a quantitative approach using a survey method. Data were collected from MSME owners through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that financial inclusion has a positive and significant effect on MSME performance, demonstrating that access to banking services, credit facilities, and digital financial platforms supports business growth and operational efficiency. Financial inclusion also significantly influences financial literacy, suggesting that greater exposure to financial services enhances business owners’ financial knowledge and skills. Furthermore, financial literacy has a significant positive effect on MSME performance and is proven to mediate the relationship between financial inclusion and performance. These findings imply that financial inclusion alone is insufficient without adequate financial literacy to ensure effective utilization of financial resources. Therefore, improving financial education alongside expanding access to financial services is essential to strengthen MSME sustainability and competitiveness. This study provides valuable insights for policymakers and financial institutions in developing strategies to enhance MSME performance through inclusive and educational financial systems.